[Cal Poly's Mustang Marching Band at Oakland Coliseum for Oakland Raiders-Pittsburgh Steelers football game, 1970] (1970)
Cal Poly's 124-member Mustang Marching Band performs at halftime show during the Oakland Raiders-Pittsburgh Steelers professional football game, played in the Oakland Coliseum.